Is a negative US agricultural trade balance a cause for concern? - Glauber, Joseph W. (American Enterprise Institute, 2025)
The rising agricultural trade deficit is a relatively recent phenomenon, but it should not be a cause for alarm. Most exported goods face little competition from imports that help consumers meet their year-round demands for fresh fruits, vegetables, and other food products.